KARAKTERISTIK MUTU DAN FISIK BIJI KOPI ARABIKA DENGAN BEBERAPA METODA PENGOLAHAN DI KABUPATEN SIMALUNGUN PROPINSI SUMATERA UTARA - Retmono Agung Winarno; Mawar Indah Perangin-angin (Agrica Ekstensia, 2020)
Some of the problems in developing coffee in Simalungun, one of which is the low quality of the product. Determinants of coffee quality are influenced by geographical indications of the origin of coffee and how the coffee is processed. The purpose of this research is to determine the quality characteristics and physical characteristics of coffee beans produced from several locations in Simalungun Regency, North Sumatra with various coffee processing methods. The material used is red cherry Arabica from several locations in Simalungun namely Raya District, Purba District, and Dolok Pardamean District, with a variety of processing methods (dry method, semi-wash method, full wash method, and honey method). The parameters observed included quality characteristics based on SNI 01-2907-2008 and physical characteristics, including seed weight, color and yield of coffee beans. The results showed that the quality characteristics of coffee beans based on SNI 01-2907-2008 varied, namely classified in quality 2, quality 3, quality 4b, quality 5, quality 6 and there were treatments on coffee beans that do not include into SNI standards. The physical characteristics produced were weight per seed ranged from 0.163 to 0.197 gram, color is fresh and green, and the yield value ranges from 13.19% to 21.48%.